The Effect of Financial Performance on Company Value Moderated by Dividend Policy - Annisa Nurul Lita; Mursidi Mursidi; Fika Fitriasari (Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine and analyze the effect of financial performance on firm value with dividend policy as a moderating variable. The object of this research is automotive and component companies listed on the Indonesia Stock Exchange in 2016-2020. The type of research used is quantitative research. The sampling technique in this study used a purposive sampling method with a total sample of 11 companies. The data analysis technique used multiple linear regression analysis using IBM SPSS Statistics v20 softwer. The results showed that there was a positive and significant effect of financial performance as a proxy for ROA and ROE on firm value. Dividend policy is not able to strengthen the relationship between financial performance and firm value.